ThesesDB – blended self-service and supervision of students’ theses - Ball, Fabian; Hummel, Thomas P.; Sonnenbichler, Andreas C.; Schweigert, Victoria-Anne (EAI Endorsed Transactions on e-Learning, 2017)
e-learning can be seen as service creation process between students and supervisors. In order to automate and enhance thesis and seminar processes at our university, we aim to increase transparency, traceability, communication, and success for our students and lecturers. Therefore, we suggest standardized process templates for students’ theses and their implementation with an IT support system. We start analyzing and designing processes for bachelor, master, and PhD theses as well as bachelor and master seminars and suggest process templates to cover these processes. To implement these standard processes, we design and implement an enhanced IT web application platform, ThesesDB. By providing a centralized view, we oer a self-service for students and supervisors in the process. Our approach is evaluated by the Computer System Usability and USE Questionnaire.
Keywords: e-learning; mentoring; process; service enhancement; supervised student publication; tutoring; workflow